„Kołakowski Bet” or Good as a Stake in the Philosophical Game of Arché - Jankowska, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The article deals with one of the most basic terms in philosophy: arché, the First Prinicple, the Origin of Everything, the source of being, truth, good and beauty. In modern Western philosophy the term is no longer obvious or necessary but it is still present in the so-called traditional, conservative or fundamentalist intellectual currents. One of the most famous contemporary representatives of such a “traditional current” is Leszek Kołakowski. The analysis of his work shows how the idea of good is related to the abovementioned term of arché. The so-called “Kołakowski Bet” is based on Dostoyevsky’s statement from “The Brothers Karamazov”: “If there is no God, everything is permitted”. Kołakowski claims that “if there is no God, it is not possible to properly use such terms as Truth or Good” because there is no general principle, no absolute understanding of the two categories. What is important, Kołakowski does not claim that God exists, he only says that God (who is here understood rather as a philosophical arché than as biblical personal God) can be the necessary condition of the validity of using the above- -mentioned terms: truth and good.